Understanding the interaction between Meloidogyne incognita and Fusarium oxysporum f. sp. passiflorae in grafted passion fruit seedlings - Silva, Aline Mayara Gonçalves Barros (2023)
The root-knot nematode, Meloidogyne incognita, and the fusariosis fungus, Fusarium oxysporum f. sp. passiflorae (FOP) cause significant damage to passion fruit crops, resulting in economic losses. One strategy for managing crop-associated soil pathogens is to explore the genetic variability of wild Passiflora species. Among these species, P. nitida is a potential species to be used as a rootstock, as it is resistant to FOP. However, it is a species extremely susceptible to M. incognita. Therefore, this is the first study to evaluate the effect of M. incognita on the growth of P. nitida and the anatomical changes caused by this infection. Three trials were conducted in a completely randomized design (CRD) in different periods, and at the end of trials, variables related to plant growth and nematode reproduction were collected. These data were statistically evaluated and treatment means were compared using the Tukey test at 5% significance level. On that occasion, root samples were also collected for histological analysis. It was observed that due to the high multiplication rate of this nematode in P. nitida, causing intense gall formation on roots and reducing plant growth, P. nitida should not be used as rootstock or even main crop in fields infested by M. incognita. In the second study, the interaction between M. incognita and FOP, inoculated individually or in combination in P. edulis f. flavicarpa seedlings grafted onto P. nitida was investigated. Two trials were carried out in a CRD, at different times, with the aim of evaluating the pathogenicity of M. incognita and FOP in these grafted seedlings. Data related to plant growth, fungus incidence, size of lesions caused by the fungus and nematode population density were collected. These data were statistically analyzed, and treatment means were compared using the Tukey test at 5% significance level. Results demonstrated neutral interaction between pathogens, because, regardless of presence of the fungus, P. nitida showed high susceptibility to M. incognita, resulting in the formation of galls on roots and reduced plant growth. Furthermore, it was observed that, even in the presence of the nematode, the size of lesions caused by FOP did not increase. It is noteworthy that the resistance of P. nitida to FOP was maintained, even in co-infection with the nematode. These findings have relevant implications for the use of P. nitida as rootstock in the FOP management.